Perlindungan Konsumen terhadap Peredaran Obat Secara Online Tanpa Izin Edar - Vina Aprilia; Nur Lailatul Maghfiroh; Salsabila Dhiya Atik; Nabyla Qutrun Nada; Alfan Hermawan; Muhammad Rizky Imami; Moh Basri Firdaus F.N7; Herdiansyah Rusman Hadi; Ainun Nur Cahyani; Marthy Meliana A.J; Dewi Rahmawati (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Health is the main capital for the growth of the nation's life. The development of trade is currently experiencing very rapidprogress, which occurs not only in the goods traded but also in the buying and selling transactions themselves. One very important component of health is the availability of medicines as part of public health services. This research aims to find out about the distribution of drugs without a distribution permit and consumer protection in terms of monitoring and taking action against drugs without a distribution permit that are sold online by the Food and Drug Supervisory Agency and the Ministry of Communication and Information. The results of the research show that the Food and Drug Supervisory Agency has made various efforts to protect the public from drugs without distribution permits that are sold online, in handling the circulation of drugs sold online, the Food and Drug Supervisory Agency collaborates with Interpol and other government agencies such as the Ministry of Communication and Informatics carries out Operation Pangea. In this operation, the Food and Drug Supervisory Agency will list websites and social media accounts that promote and market drugs without a distribution permit to be submitted to the Ministry of Communication and Information for blocking. A distribution permit is preventive supervision as a form of protection for consumers carried out by the Food and Drug Supervisory Agency before the drug circulates in the community. So it is reasonable to suspect that if a drug does not have a distribution permit, the drug has not been tested for safety, efficacy and quality aspects.